2017
DOI: 10.1002/ajh.24623
|View full text |Cite
|
Sign up to set email alerts
|

Increased healthcare use up to 10 years among relapse‐free Hodgkin lymphoma survivors in the era of intensified chemotherapy and limited radiotherapy

Abstract: With today's excellent cure rates for Hodgkin lymphoma (HL), the number of long-term survivors is increasing. This study aims to provide a global assessment of late adverse effects for working-age HL survivors treated with contemporary protocols (combination chemotherapy and limited radiotherapy). From Swedish nationwide registers we identified 1017 HL survivors diagnosed in 2000-2009, aged 18-60 years (median 32) and surviving at least one year post-diagnosis, and 4031 age-, sex-, and calendar-year-matched po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 53 publications
4
20
0
Order By: Relevance
“…10,12,26,33,34 Our finding that the excess hospital use among survivors is mainly driven by the relapsing individuals is in line with a few other previous investigations. 26,35,36 Results similar to the present study were recently reported in a Danish population-based study of 1768 5-year survivors of HL, diagnosed at ages 15-39 years in the period 1943-2004. 37 That study overlapped with the present investigation for the subset of 15-24-year-old Danish patients diagnosed between 1990 and 2004, who survived their disease by 5 years or more, but included neither children, nor outpatient data or clinical information, such as disease stage, and further, only approximated relapse-status.…”
Section: Discussionsupporting
confidence: 92%
“…10,12,26,33,34 Our finding that the excess hospital use among survivors is mainly driven by the relapsing individuals is in line with a few other previous investigations. 26,35,36 Results similar to the present study were recently reported in a Danish population-based study of 1768 5-year survivors of HL, diagnosed at ages 15-39 years in the period 1943-2004. 37 That study overlapped with the present investigation for the subset of 15-24-year-old Danish patients diagnosed between 1990 and 2004, who survived their disease by 5 years or more, but included neither children, nor outpatient data or clinical information, such as disease stage, and further, only approximated relapse-status.…”
Section: Discussionsupporting
confidence: 92%
“…For example, unbalanced chromosomal abnormalities may result in the deletion of tumor suppressor genes or inactivation of genes involved in DNA repair. In addition, balanced exchanges could allow the survival of carrier cells by affecting the function of genes important for preventing cancer development, modifying the expression of oncogenes, or tumor suppressor genes, and thus, permitting the occurrence of SMN in these patients (Glimelius et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite showing high survival rates for relapse-free individuals and less fatal treatment toxicity, our data still motivate follow-up (Glimelius et al, 2017). Fatal late effects may develop beyond two decades of follow-up.…”
Section: Discussionmentioning
confidence: 74%